A Note on Fourth Five-Year Plan Orissa - Planning Commission (Planning Commission, 1964)
The present note attempts to merely highlight some of the basic considerations that should underline the approach to planning in Orissa. It docs not endeavour to give any detailed estimates of the total outlay and its distribution for die Fourth Plan nor provide any defined volumes of investments required for achieving the objectives that may be laid down. The note confines itself to a discussion of the state of under-development in Orissa with a view to bringing out the need for a reorientation in our outlook to planning.
Government of Orissa Planning and Co-ordination Department